Čista teorija prava kot izziv - Zadravec, Mojca (Pravnik, 2015)
The main issues of the legal theory are: what gives validity to the law, where does it derive from, and what is its foundation (ultimate or supreme legal norm, which gives it the validity). These questions have been dealt with also by Hans Kelsen and his circle, among whom was also Leonid Pitamic. Academic Marijan Pavčnik's book Pure theory of law as a challenge is a display of some of Pitamic's concerns, ideas, thoughts and objections, which highlight some aspects of development of pure theory of law and Pitamic's contribution and surplus in it.
Keywords: law; ocene in poročila; Pavčnik, Marijan: Čista teorija prava kot izziv; pravo; teorija; theory